Height, weight and BMI percentiles and nutritional status relative to the international growth references among Pakistani school-aged children - Mushtaq Muhammad Umair; Gull Sibgha; Mushtaq Komal; Abdullah Hussain Muhammad; Khurshid Usman; Shahid Ubeera; Shad Mushtaq Ahmad; Akram Javed (BMC, 2012)
Abstract Background Child growth is internationally recognized as an important indicator of nutritional status and health in populations. This study was aimed to compare age- and gender-specific height, weight and BMI percentiles and nutritional status relative to the international growth references among Pakistani school-aged children. Methods A population-based study was conducted with a multistage cluster sample of 1860 children aged five to twelve years in Lahore, Pakistan. Smoothed height, weight and BMI percentile curves were obtained and comparison was made with the World Health Organization 2007 (WHO) and United States' Centers for Disease Control and Prevention 2000 (USCDC) references. Over- and under-nutrition were defined according to the WHO and USCDC references, and the International Obesity Task Force (IOTF) cut-offs. Simple descriptive statistics were used and statistical significance was considered at P < 0.05. Results Height, weight and BMI percentiles increased with age among both boys and girls, and both had approximately the same height and a lower weight and BMI as compared to the WHO and USCDC references. Mean differences from zero for height-, weight- and BMI-for-age z score values relative to the WHO and USCDC references were significant (P < 0.001). Means of height-for-age (present study: 0.00, WHO: -0.19, USCDC: -0.24), weight-for-age (present study: 0.00, WHO: -0.22, USCDC: -0.48) and BMI-for-age (present study: 0.00, WHO: -0.32, USCDC: -0.53) z score values relative to the WHO reference were closer to zero and the present study as compared to the USCDC reference. Mean differences between weight-for-age (0.19, 95% CI 0.10-0.30) and BMI-for-age (0.21, 95% CI 0.11-0.30) z scores relative to the WHO and USCDC references were significant. Over-nutrition estimates were higher (P < 0.001) by the WHO reference as compared to the USCDC reference (17% vs. 15% overweight and 7.5% vs. 4% obesity) while underweight and thinness/wasting were lower (P < 0.001) by the WHO reference as compared to the USCDC reference (7% vs. 12% underweight and 10% vs. 13% thinness). Significantly lower overweight (8%) and obesity (5%) prevalence and higher thinness grade one prevalence (19%) was seen with use of the IOTF cut-offs as compared to the WHO and USCDC references. Mean difference between height-for-age z scores and difference in stunting prevalence relative to the WHO and USCDC references was not significant. Conclusion Pakistani school-aged children significantly differed from the WHO and USCDC references. However, z score means relative to the WHO reference were closer to zero and the present study as compared to the USCDC reference. Overweight and obesity were significantly higher while underweight and thinness/wasting were significantly lower relative to the WHO reference as compared to the USCDC reference and the IOTF cut-offs. New growth charts for Pakistani children based on a nationally representative sample should be developed. Nevertheless, shifting to use of the 2007 WHO child growth reference might have important implications for child health programs and primary care pediatric clinics.